Efisiensi Tular Benih Squash mosaic virus pada Cucurbitaceae - Susanti Mugi Lestari; Endang Nurhayati (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Infection of viruses on Cucurbitaceae may cause high yield and economic losses. Squash mosaic virus is a seed borne virus and among the most important virus infecting Cucurbitaceae. The aims of these research was to detect infection of several viruses on Cucurbitaceae and to examine seed transmission efficiency of SqMV. Detection of Cucumber mosaic virus (CMV), Squash mosaic virus (SqMV), Watermelon mosaic virus-2 (WMV-2), Zucchini yellow mosaic virus (ZYMV), and Tobacco ringspot virus (TRSV) from field samples and seeds was conducted using Indirect-ELISA method. Infection of CMV, SqMV and ZYMV was detected from field samples. Seed transmission of SqMV on commercial seeds of bottle gourd, watermelon, zucchini, cabocha, cucumber, and melon was 13, 13, 33, 73, 100, and 100%, respectively. Seed transmission of ZYMV was only occurred on bottle gourd and zucchini, i.e. 13.3% and 26.67%, respectively. Infection of SqMV through F2 seed was determined from cucumber, bottle gourd, and melon, i.e. 93, 100, and 100%, respectively. Therefore, the status of SqMV as quarantine pest should be evaluated since SqMV was already found in West Java.